Microscopic Analysis of the Pollen Morphology of Some Garcinia Species - Yapwattanaphun, Chinawat (Microscopy and Microanalysis Research – The Journal of The Microscopy Society of Thailand, 2019)
Garcinia (Family Clusiaceae) is a large genus comprising almost 400 tropical trees and shrubs, and the pollen of most of them has not been studied. In this research the pollen morphology of 8 Garcinia species were studied by light microscope and scanning electron microscope (SEM). The pollen grains were all classified as small; the smallest measuring approximately 12 x 19 µm and the largest 25 x 27 µm. All were spheroid or sub-spheroid. No apertures were visible on 6 of the species, while the other 2 species were 6-colporate. A diversity of exine sculpturing patterns were observed: 3 species were echinate (with spines), 2 were psilate (smooth), one was micro echinate (with very small spines), one was rugulate (with uneven protrusions), and one had an unusual sculpturing pattern that we characterized as “gemmate-micro echinate” because it has gemma, or protuberances of diverse shape and size, and on the surface of these gemma there are tiny spines. The results confirm the finding that Clusiaceae is a eurypalynous family in which the pollen grains show wide diversities of ornamentation patterns and numbers of apertures, even among species in the same genus. The data may be of use in plant systematics and classification.